From Cooperation to Competition: The Evolution of the US-China Relations since the Cold War - Hasim Turker (ASIAN Journal of International Peace & Security (AJIPS), 2023)
This study examines the intricate dynamics between the United States and China in the post-Cold War era, focusing on their evolving relationship under the aegis of various American and Chinese presidencies. The paper pursues two primary objectives; to discern the factors driving the transition from cooperation to competition in the bilateral relationship, and; to scrutinize how these shifts manifested under successive administrations in both countries. Employing a Realist approach anchored in balance of power theory, the study uses content analysis to critically assess a diverse array of primary and secondary sources, including but not limited to, policy documents, speeches, and scholarly papers. The analysis spans multiple domains—economic, technological, geopolitical, and human rights—offering a granular look at the policies and strategies each administration employed to manage this complex relationship. By incorporating the Chinese perspective, the paper enriches the dialogue surrounding the US-China relations, providing a more balanced and nuanced understanding. The study culminates in a comprehensive appraisal of the current state of relations, along with insights and recommendations for future policy and scholarly exploration. This research serves as a significant contribution to existing literature, shedding new light on the complexities and unexplored avenues in one of the most critical bilateral relationships shaping the modern international order.